Remote specialist assessment for intravenous thrombolysis of acute ischaemic stroke by telephone. Issue 9 (27th October 2011) - Rudd, Matthew; Rodgers, Helen; Curless, Richard; Sudlow, Mark; Huntley, Stuart; Madhava, Badanahatti; Garside, Mark; Price, Christopher I
Abstract : Objective: To describe the process, efficacy and safety of intravenous thrombolysis for acute ischaemic stroke in an emergency department (ED) setting with remote specialist support through structured telephone consultation. Design: Retrospective case series. Setting: Three EDs within a single stroke service in northern England. Participants: Patients with acute stroke given intravenous thrombolytic therapy between 6 September 2007 and 1 October 2010. Outcome measures: Combined death and dependency at 90 days (0–2 on the modified Rankin Scale for a good outcome vs 3–6 for a poor outcome), door-to-needle time, neurological impairment and presence of treatment related haemorrhage. Results: 192 patients received intravenous thrombolysis. 94/178 (53%) were treated after remote specialist assessment. Data available from 178 patients showed similar proportions with a good outcome after each mode of assessment (56% in person and 48% by telephone). The median door-to-needle time was 8 min faster in the group assessed in person (65 vs 73 min by telephone) but there was no difference in neurological outcome or symptomatic haemorrhage. After review in person, the stroke specialist tended to treat patients with a higher median modified Rankin Scale (1 vs 0 by telephone). Conclusion: In a single stroke service the clinical outcomes of treatment with intravenous thrombolysis were similar whether assessment was performed after specialist review in person or via a telemedicine service consisting of ED staff training, telephone consultation and remote review of brain imaging by a stroke specialist.